Results of novel theoretical approaches show a possible underestimation of building materials contribution to indoor radon levels - Maiorana Andrea; Di Carlo Christian; Ampollini Marco; Antignani Sara; Caprio Mario; Carpentieri Carmela; Bochicchio Francesco (Scientific Reports)
Abstract The mathematical modelling represents one of the main possibilities to assess the radon gas coming out from building structures in a dwelling, especially in preventive strategies. The formulations available depends on environmental conditions and building characteristics and they might require a wide set input parameters as well as significant computational capabilities: consequently, only a simplified formulation has been used throughout the years. This work quantified the differences resulting from the application of the simplified formulation instead of the exact ones to assess the radon exhalation rate and the corresponding radon activity concentration established indoors, relative to a reference room. The numerical impact of the simplified approach has been analysed by varying the main building structure parameters. The simplified approach has been shown to provide accurate results—the error on radon activity concentration is below 10%—when the pressure gradient across the building structure is negligible and the building material radon diffusion length is low, so for partition walls. For perimetral walls, especially when the pressure-gradient across the building envelope is not negligible and for high permeable building materials, the simplified approach may return even severe (about 50%) underestimation of the resulting radon activity concentration indoors.